EVALUATIONS OF NEW GENERATION ANTI-DRUG PROJECT UNDER TANGPOON MUNICIPAL KINDERGARTEN SCHOOL CHALOEM PHRA KIAT DISTRICT NAKHON SI THAMMARAT - Jindawat, Pattaratorn; Chanakul , Benchaporn; Prasan , Anotai (Journal of Educational Review Faculty of Education in MCU, 2025)
This research article aims to evaluate the reactions of the project, the learning of the project, the behavior of the project and the results of the New Generation Anti-drug Project at Tangpoon Municipal Kindergarten School, located in Chaloem Phra Kiat District, Nakhon Si Thammarat Province. This research is a mixed method, consisting of; 1) The quantitative research involved data collection through purposive sampling of relevant participants. The sample group consisted of 90 participants, including school administrator, teachers, and students from primary levels 5-6. Data were analyzed using mean, standard deviation and t-test.2) The qualitative research involved in-depth interviews of relevant participants. Consisted of 5 participants, including the school administrator, project owner, teachers teaching primary levels 6, student-council president, and student affairs teacher. Data were analyzed using content analysis. The research findings revealed that: 1) The learning of the project: Overall, the reaction was at a high level. When considering each aspect individually, the aspect with the highest mean was the speakers, followed by audio-visual facilities, and the aspect with the lowest mean was the activity process and steps. 2) The behavior of the project: It was found that the knowledge and understanding gained from participating in the " New Generation Anti-drug Project at Tangpoon Municipal Kindergarten School showed an average score of 5.12 before the training and 8.31 after the training. A dependent T-test comparison revealed that the scores after the training were significantly higher than the scores before the training, with a t-value of 18.57, which was statistically significant at the .05 level. 3) The behavior of the project: Overall, the behavior was at a high level. When considering each aspect individually, the aspect with the highest means was trained students completing tasks on time, followed by trained students listening to others' opinions, and the aspect with the lowest means was trained students presenting their work in an interesting way. 4) The results of the New Generation Anti-drug Project at Tangpoon Municipal Kindergarten School: Overall, the outcomes were at a high level. When considering each aspect individually, the aspect with the highest means was participants demonstrating public consciousness, dedication, and sacrifice for the organization and society. This was followed by participants showing love and loyalty to the organization. The aspect with the lowest means was participants being able to apply drug-related knowledge to happily coexist with others. Qualitative findings showed that participants were actively involved in activities. The educational institution organized information boards and publicized the project, typically in the morning before the flagpole assembly. The administrators recognized the benefits of this training, which positively impacted participants in terms of correct knowledge and understanding. This influenced their lifestyle behaviors and provided them with knowledge about the dangers of drugs and how to avoid substance abuse. Students were able to effectively apply drug-related knowledge to coexist with others.